The Honey for The Treatment of Diabetic Foot: A Literature Review - Hinin Wasilah; Lisnawati Nur Farida; Zahri Darni (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Background: Honey known as wound healer, but the use of honey for diabetes population is lack. Scientific studies needed to provide enough evidence to justify the benefits of honey for the treatment of diabetic foot ulcers. Aims: To identify the benefit of honey as healing diabetic foot ulcer. Methods: The author was used PICO question as the first step of this study, then the second step was searching the articles from several databases. The inclusion and exclusion criterias were using only honey as a diabetic foot treatment on human, randomized control trial study or quasy experimental study, published less than 10 years ago (2009 – 2019), available in English and provide full text. Meanwhile, for the exclusion criteria were literature review, systematic review or meta-analysis study, using honey as a treatment to animal such as rat and rabbit, combine honey with another treatment. By using PRISMA guideline, researchers were systematically review several articles from 4 databases. Results: After conducted search strategy by using Boolean search strategy, 4 articles were included. The articles used different types of honey and the population ranged from 8 to 63 peoples. According to the results, majority of study showed honey is effective as wound healer and safe Conclusion:  Honey wound dressing is an option for managing diabetic foot Recommendation: As a nurse, we can offer the honey as an effective treatment or intervention tools for targeted patients or populations